Pengaruh Substitusi Tepung Bonggol Pisang terhadap Komposisi Proksimat dan Daya Terima Butter Cookies - Ihsanti, Elsa Nurul; Kurnia, Pramudya; Sofyan, Aan; Purwani, Eni (Universitas Malahayati, 2024)
ABSTRACT Banana weevil flour can be used as a substitute because the composition of banana weevil flour is close to that of wheat and even contains several nutrients that are higher than wheat flour such as energy, calcium, phosphorus, iron and vitamin C. This research aims to determine the effect of banana weevil flour substitution on Proximate composition and acceptability of butter cookies. This research is a type of quantitative research with research methods, namely experimental using a Completely Randomized Design with 4 treatments and 2 repetitions of the variables tested, namely proximate and acceptability used in this research. A total of 30 people were used as research respondents. Proximate test data and acceptability were analyzed using One Way Anova, and continued with Duncan's follow-up test (DMRT) with a confidence level (α = 0.05). The results of the research on the proximate test of the moisture content parameters of butter cookies through substitution of 0%, 15%, 25% and 35% respectively obtained results of 4.05%, 4.61%, 4.64% and 4.96% with results sig (p=0.104). The results obtained can be seen that there is no effect of banana weevil flour substitution on water content. The results of the acceptability test on the overall indicator with a value range of 5.87 - 6.52 were given by the panelists, which means they are in the somewhat like to like category. Treatment S1 has the highest value, namely 6.52 with a ratio of banana weevil flour and wheat flour of 0%:100%. The conclusion was that butter cookies substituted with banana hump flour had the best water content in the S2 treatment. Meanwhile, the best receptivity was in the S2 treatment. Keywords: Banana Weevil Flour, Proximate, Acceptability, Butter Cookies ABSTRAK Tepung bonggol pisang dapat dimanfaatkan sebagai substitusi karena komposisi tepung bonggol pisang mendekati terigu bahkan terdapat beberapa zat gizi yang lebih tinggi dari tepung terigu seperti energi, kalsium, fosfor, zat besi, dan vit C. Penelitian ini bertujuan untuk mengetahui pengaruh substitusi tepung bonggol pisang terhadap komposisi proksimat dan daya terima butter cookies. Penelitian ini merupakan jenis penelitian kuantitatif dengan metode penelitian yaitu eksperimental dengan menggunakan Rancangan Acak Lengkap dengan 4 perlakuan dan 2 kali pengulangan pada variabel yang diuji yaitu proksimat dan daya terima dipergunakan di penelitian ini. Sebanyak 30 orang dijadikan sebagai responden penelitian. Data uji proksimat dan daya terima analisis menggunakan One Way Anova, dan dilanjutkan uji lanjut Duncan (DMRT) dengan tingkat kepercayaan (α = 0,05) . Hasil penelitian pada uji proksimat parameter kadar air butter cookies melalui substitusi 0%, 15%, 25%, serta 35% masing-masing diperoleh hasil 4,05%, 4,61%, 4,64% dan 4,96% dengan hasil sig (p=0,104). Hasil yang didapatkan dapat dilihat bahwa tidak terdapat pengaruh substitusi tepung bonggol pisang terhadap kadar air. Hasil uji daya terima pada indikator keseluruhan dengan rentang nilai 5,87 - 6,52 diberikan panelis yang berarti berada pada kategori agak suka hingga suka. Perlakuan S1 mempunyai nilai tertinggi yakni 6,52 dengan nilai perbandingan tepung bonggol pisang dan tepung terigu 0%:100%. Kesimpulan yang didapatkan bahwa butter cookies dengan substitusi tepung bonggol pisang kadar air terbaik pada perlakuan S2. Sedangkan daya terima terbaik pada perlakuan S2. Kata Kunci: Tepung Bonggol Pisang, Proksimat, Daya Terima, Butter Cookies